2011
DOI: 10.4238/2011.december.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2C19*3 gene polymorphism with breast cancer in Chinese women

Abstract: ABSTRACT. Cytochrome P450 (CYP) 2C19 metabolizes arachidonic acid to biologically active epoxyeicosatrienoic acids, which significantly promote proliferation of cancer cells in vitro and in vivo. We looked for a possible association between human CYP2C19*3 gene polymorphism and breast cancer in the Chinese Han population. In a Chinese Han case-control study of breast cancer patients (N = 600) and age-and gender-matched healthy controls (N = 600), we investigated polymorphism in the CYP2C19 gene by PCR-RFLP ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
1
11
1
1
Order By: Relevance
“…The CYP2C9*2 allele has not been detected in a Chinese population, and the frequency of the CYP2C9 * 3 allele was 2–2.6% [22,24]. The CYP2C19*2 mutant allele was found at a frequency of 21.9% in this study, which is not significantly different from previous reports in the literature for Caucasians (15 20%) [1,7] and Japanese (26.7%) [25].…”
Section: Resultscontrasting
confidence: 77%
“…The CYP2C9*2 allele has not been detected in a Chinese population, and the frequency of the CYP2C9 * 3 allele was 2–2.6% [22,24]. The CYP2C19*2 mutant allele was found at a frequency of 21.9% in this study, which is not significantly different from previous reports in the literature for Caucasians (15 20%) [1,7] and Japanese (26.7%) [25].…”
Section: Resultscontrasting
confidence: 77%
“…Rat Mcs3 was found to contain sequence orthologous to human 11q13/14 , which contains multiple genes and is amplified in a subset of female breast carcinomas with poor prognosis (Tsuda et al 1989). In addition to a functional correlation with breast cancer development, studies reporting genetic associations of CYP2C19 variants with breast cancer susceptibility have been published (Justenhoven et al 2009; Sangrajrang et al 2009; Gan et al 2011). …”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that the CYP2C19*3 variant may be associated with breast cancer risk in Chinese Han women (Gan et al 2011). Neither the CYP2C19*17 variant, which results in a rapid metabolizer phenotype, nor the CYP2C19*2 variant were associated with breast cancer risk in population-based studies of women of European descent; however, CYP2C19*17 was associated with decreased risk in women using hormone replacement therapy for >10 yr (Justenhoven et al 2009, 2012; MARIE-GENICA Consortium on Genetic Susceptibility for Menopausal Hormone Therapy Related Breast Cancer Risk 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that functional genetic variants of the CYP2C19 are associated with overall breast cancer risk and HRT-related breast cancer risk (Gan et al, 2011; Justenhoven et al, 2012). It is of note that these findings in two independent studies show similar effects.…”
Section: Phase I and Ii Enzymes In Association With Breast Cancer Riskmentioning
confidence: 99%
“…It is of note that these findings in two independent studies show similar effects. The variant CYP2C19 *3 (rs57081121) which lead to a decreased activity of the CYP2C19 has been associated with increased risk in Asians (Gan et al, 2011) and the variant CYP2C19 *17 (rs12248560) causing an ultra rapid metabolizer phenotype leads to a decreased HRT-related breast cancer risk in Europeans (Justenhoven et al, 2012). It is known that CYP2C19 catabolizes estrogens and progesterone (Yamazaki and Shimada, 1997; Cheng et al, 2001; Cribb et al, 2006) and the reported results suggest that increased metabolic activity of the CYP2C19 lowers endogenous hormone levels leading to a decreased risk.…”
Section: Phase I and Ii Enzymes In Association With Breast Cancer Riskmentioning
confidence: 99%